Branding specificities of the Armenian “Velvet Revolution” - Asriyan, Elina; Melkonyan, Nvard (Przegląd Wschodnioeuropejski, 2019)
The so-called modern-day “colored revolutions” implemented in varous parts of the globe have their specificities. The development of social communication and its changes in quality have in fact influenced the implementation of “colored revolutions”, as well as its technologies. In the process of branding the Armenian velvet revolution, several important tasks were set: to make actions of disobedience and protests recognizable as revolutionary actions, to present the velvet revolution as a continuation and result of protest actions that were taking place in the country over the past ten years, and the last task concerned the need to unite different social segments around a common idea. The success and desire of a velvet revolution as a brand was conditioned by the following: considering the psychological peculiarities of perception of a person, presenting the revolution as the only opportunity for addressing the political problems in the country and pointing out succeeded key messages, conformity with the target audience’s desires, social needs, expectations, and ideas about future; effective and balanced communication mechanisms with the target audience.